AN ANALYSIS OF THE DIFFERENCES BETWEEN COMIC AND MOVIE BY STAN LEE: IRON MAN - Kevin Oroh; Nurmin Samola; Paula Hampp (English Education Department, 2022)
This research aims to find out the differences between comics and movie by using a qualitative method, effective to describe the problem and give more explanation about this comic and movie Iron Man. This research was conducted in Comic (Tales of Suspense: Iron Man) and Movie Iron Man (2008). To fulfill the research objective, the researcher took an experimental study involving a sample of a movie with a duration of 2 hours 6minutes and a comic strip of 13 pages. Data is obtained through analysis in books and comics, reading, and seeing the problems obtained. The data in the comics show more past events at that time than the data in the movie. in the comics it shows realistic events in the 1963 era and the values or data shown in the movie are more into the modern era. Based on the results of the research, the researcher concludes that the comics and the Iron Man film have differences that make each story with the right elements, stories that have suggestions through time